2017
DOI: 10.1017/s1368980017001124
|View full text |Cite
|
Sign up to set email alerts
|

The fruit and vegetable intake of young Australian adults: a population perspective

Abstract: Fruit and vegetable intake is suboptimal among Australian young adults. An age-appropriate campaign is recommended to target increased consumption, particularly for those aged 18-24 years, with opportunity to promote increased variety and consumption across the day.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

8
56
5
3

Year Published

2018
2018
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 54 publications
(72 citation statements)
references
References 55 publications
(56 reference statements)
8
56
5
3
Order By: Relevance
“…While females and domestic students consumed fruit and vegetables more frequently than males, and international students consumed breads and cereals more frequently than domestic students. In terms of age, the poorer eating behaviours among younger students is supported by national and international study findings where 18 to 24 year olds have been found to consume lower fruit and vegetables and have worse dietary pattern scores compared with adults 25 years and above . This demonstrates the importance of targeting eating behaviours in emerging adults .…”
Section: Discussionmentioning
confidence: 88%
“…While females and domestic students consumed fruit and vegetables more frequently than males, and international students consumed breads and cereals more frequently than domestic students. In terms of age, the poorer eating behaviours among younger students is supported by national and international study findings where 18 to 24 year olds have been found to consume lower fruit and vegetables and have worse dietary pattern scores compared with adults 25 years and above . This demonstrates the importance of targeting eating behaviours in emerging adults .…”
Section: Discussionmentioning
confidence: 88%
“…Age and sex were the biggest predictors of whether Australian children meet the recommended daily number of serves of fruit and vegetables, with children from 4 to 18 and boys, in particular, at greatest risk of not meeting the recommendations for both fruit and vegetables. These sex‐specific differences have been found in young adults in Australia suggesting that interventions that start early in childhood are needed. We found little evidence that SES is a significant factor predicting the difference in meeting vegetable recommendations, and this suggests that health promotion interventions may be useful across demographic strata with a national approach and a refocus on vegetables instead of “fruit and vegetables” may be needed.…”
Section: Discussionmentioning
confidence: 89%
“…In all age groups, the intakes of wholegrain were the lowest for adolescents [ 37 ]. Among adults, the intakes of fruit and vegetables were lower in males [ 38 ], the intakes of discretionary foods and beverages were higher in young adults and males [ 39 ], and the diet quality score based on the 2013 Australian Dietary Guidelines was lower for young adults and males [ 40 ]. A lower food literacy may contribute to the poorer diets observed for males.…”
Section: Discussionmentioning
confidence: 99%